Dampak Model Problem-Based Learning pada Kemampuan Pemecahan Masalah IPA Siswa SMP: Analisis Systematic Literature Review - Irma Lutfia; Rizki Arumning Tyas (Journal of Progressive Science Education, 2025)
This study aims to describe the influence of implementing the Problem-Based Learning (PBL) model on junior high school students' problem-solving abilities thru a systematic review of various previous studies. This study uses the Systematic Literature Review (SLR) method, referring to the PRISMA 2020 guidelines. A total of ten relevant articles were selected based on inclusion criteria, which included research examining the application of the PBL model in science learning at the junior high school level. The research results showed that the consistent application of PBL had a positive impact on improving students' problem-solving abilities. Additionally, PBL also impacts improved learning outcomes, concept mastery, and higher-order thinking skills relevant to the demands of 21st-century learning. Cross-study analysis also revealed disparities in the distribution of science content, with research focusing more on physics content, while biology appeared in limited quantities and chemistry content was not identified in the articles meeting the criteria. These findings are also influenced by the limited number of articles and the scope of the databases used. Thus, PBL can be recommended as an effective learning model for developing problem-solving skills in science learning at the junior high school level.